Effect of N and K fertilizers on nutrient leaching and groundwater quality under oil palm - Ah Tung, Petronella Gerald; Yusoff, Mohd Kamil (2009)
The major nutrients required for oil palm are mainly nitrogen, phosphorus and potassium. When applying fertilizers to the palms, our goal is to maximize nutrient uptake by the palms from the fertilizers for optimum growth and production. Unfortunately, losses of applied fertilizer to the atmosphere or through runoff and leaching generally occur as unintended consequences of fertilization. One of major pathway of fertilizer losses is by leaching in which nutrients are moved down the soil profile until they reach a depth where there are no palm roots. Consequently this can be of serious environmental concern in areas where nutrients can enter groundwater. Nitrogen and potassium are the most nutrients at risk, because of the rather weak adsorption of ammonium and potassium ions and nil adsorption for nitrate (Corley and Tinker, 2007). It has been reported that leaching losses for a clay loam soil under mature palm were about 2-6% of the applied N and K fertilizers and 1-3% for P fertilizer (Foong, 1993).